A Bibliometric Analysis of Critical and Creative Thinking in Elementary School Mathematics Learning - Aswin; Al Jupri; Dadang Juandi; Suhendra; Eyus Sudihartinih; Andi Sri Hardiana (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2026)
Through a bibliometric approach, this study aims to analyze trends, main focuses, and potential future research themes related to critical and creative thinking skills in mathematics learning at the elementary school level. The data were obtained from the Scopus database covering the years 1997–2025 with the search keywords